(untitled) (Medical Forum Monthly, 2024)
Objective: Gingivitis is a commonly occurring preventable disease prevalent among the people of Pakistan. Gingivitis is a disease of the gums which if left untreated can turn into a more extreme disease known as periodontitis. The objectives of the study were to assess the frequency of gingivitis in patients visiting secondary care hospital in Gadap region in Karachi, Pakistan and to study the level of gingivitis and its associated risk factors in these patients. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the patients attending out-patient department of private secondary care dental hospital in Gadap town, Karachi, Pakistan from January till June 2018. Materials and Methods: Multistage sampling technique was used; initially stratified sampling was done for making strata of male and female which was followed by non-probability purposive sampling for selection of the participants. Results: A total of 387 patients were examined of which 208 (53.7 %) were males and 179 (46.3%) were females. The age group ranged from 30 to 39 were seems to be the highest among all other ranges with total of 131 patients out of 387 and second highest age group was form 40 to 49 with total of 127 patients respectably. A highly significant association (p value < 0.001) between gingivitis and gender of the patients was found. A significant association (p value < 0.05) was found between the degree of gingivitis and tobacco chewing or tobacco containing products. A highly significant association (p value < 0.001) between gingivitis and the bleeding gums during brushing was observed. Majority of the patients (n=139, 84.2) with bleeding gums during brushing had severe inflammation as well. Conclusion: It is indicated from the study that the poor oral hygiene and improper eating habit have a negative impact on the periodontal condition and that can leads to severe destructive condition of oral tissue.